please explain me how to do this As x + 4x — 3 cannot be easily factorised, we need to transform the equation ** + 4x – 3=0 into

Question

please explain me how to do this
As x + 4x — 3 cannot be easily factorised, we need to transform the equation
** + 4x – 3=0 into the form (x + a)2 = b as follows:
ATTENTION
x² + 4x-3=0
x? + 4x = 3
(rewrite the equation such that the constant term is
on the RHS of the equation)
Alternatively, we can compl
the square by:
² + 4x 3 =
*****+()* – 3-(
(12/ (add
(4)
to both sides of the equation to complete [2++(371-47
the square for the LHS)
ta
-4
x2 + 4x + 22 = 3 + 22
(x + 2)² = 7
(factorise the expression on the LHS and simplify
the RHS)
or
x + 2 = +7
(take the square roots on both sides)
x + 2 = 7
x + 2 = -17
x = √7-2
= 0.65 (to 2 d.p.)
= -4.65 (to 2 d.p.)
x = -√7-2
..x=0.65 or x = -4.65
where p and​

in progress 0
Isabelle 3 weeks 2021-10-04T02:34:19+00:00 1 Answer 0 views 0

Answers ( )

    0
    2021-10-04T02:35:39+00:00

    Answer:

    please mark the brainlests I am following you. . . . . …. .. . . . . . .. . . . . . . . . . . .. . . . . . .. . . ?

Leave an answer

Browse
Browse

18:9+8+9*3-7:3-1*13 = ? ( )